Keratins as regulators of colonocyte mitochondria and intestinal barrier function - Heikkilä, Taina (My University, 2020)
Keratins are part of a filamentous structures forming the cytoskeleton. Keratins provide structural support and are involved in several cell processes. Keratins are known to affect mitochondrial function in the liver but the role in mitochondrial function in the colon is less known. In previous studies K8 knockout (K8–/–) in Caco-2 cells leaded to diminished mitochondrial respiration and decreased levels mitochondrial and caveolar calcium (Ca2+) levels. In this study the involvement of K8 on mitochondrial function was further examined in K8–/– Caco-2 cells by microplate reader assays to determine the levels of mitochondrial membrane potential (MMP) and cardiolipin (CL), which are both needed for normal mitochondrial function. Mitochondrial distribution was studied by immunohistochemistry and mitochondrial motility by staining and live cell imaging. Caveolin proteins are involved in Ca2+ signaling and mitochondrial function. Therefore, distribution of caveolin-1 (Cav1) was studied by immunostaining. Intestinal barrier function is the ability of the epithelial cell layer of the intestinal wall to selectively pass substances across. The role of K8 in barrier function in Caco-2 cells was studied with a Cellzscope+ device. Loss of K8 in Caco-2 leads to decreased levels of MMP and CL, increased mobility of mitochondria and fragmented mitochondrial network as well to an aggregation of Cav1 protein, all which may affect to the energy metabolism in Caco-2 cells. Barrier formation was decreased and delayed in K8–/– compared K8+/+ Caco-2 cells. In conclusion, this study further support findings on the role of keratins in regulation of mitochondrial morphology and function.
Keywords: Keratin 8, Mitochondria, mitochondrial membrane potential, cardiolipin, caveolin-1, intestinal barrier function